Azapirone 5-HT1A receptor partial agonist treatment for major depressive disorder: systematic review and meta-analysis. Issue 11 (21st November 2013) - Kishi, T.; Meltzer, H. Y.; Matsuda, Y.; Iwata, N.
Abstract : Background: A meta-analysis of the serotonin1A (5-HT1A ) receptor partial agonist of the azapirone class as an anxiolytic drug for the treatment of major depressive disorder (MDD) has not previously been reported. Method: We carried out a systematic review of the literature available in PubMed, the Cochrane Library database and PsycINFO up to 12 October 2013, and conducted a meta-analysis of randomized controlled trials (RCTs) comparing 5-HT1A agonists with placebo and RCTs of 5-HT1A agonist augmentation therapies for MDD treatment. We calculated the risk ratio (RR), number needed to treat (NNT)/number needed to harm (NNH) and 95% confidence intervals (CIs). Results: Fifteen RCTs comparing 5-HT1A agonists with placebo (total n = 2469, four studies with buspirone, seven with gepirone, three with ipsapirone and one with zalospirone) were identified. Pooled 5-HT1A agonists had significantly more responders (RR 0.74, 95% CI 0.65–083, p < 0.00001, NNT = 6, 12 trials, n = 1816) than placebo. Pooled 5-HT1A agonists were superior to placebo in discontinuation due to inefficacy (RR 0.49, p = 0.02, NNH = 16, p = 0.03, 10 trials, n = 1494) but were inferior to placebo in discontinuation due to side-effects (RR 1.88, p < 0.0001, NNH = 17, p = 0.001, 13 trials, n = 2196). However, all-cause discontinuation was similar in both groups (RR 0.99, p = 0.85, 14 trials, n = 2402). Four 5-HT1A agonist augmentation studies were identified (total n = 365, three buspirone studies and one tandospirone study). There were no statistically significant effects of 5-HT1A agonist augmentation therapies on response rate (RR 0.98, p = 0.85, four trials, n = 341). 5-HT1A agonist-related side-effects including gastrointestinal symptoms, dizziness, insomnia, palpitation, paresthesia and sweating were greater than with placebo ( p < 0.00001 to p = 0.03). Conclusions: Our results suggest that 5-HT1A agonist has a more beneficial effect on MDD than placebo, but has several side-effects.